Potensi Pemanfaatan Serbuk Plastik Dan Biomassa Sebagai Bahan Bakar Alternatif - Basir, Muhammad; Mangalla, Lukas Kano; Sisworo, Raden Rinova (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Every year the use of fossil fuels has increased, which requires finding alternative energy sources to replace fossil fuels. The existence of plastic waste, especially HDPE plastic and rice husks, is a potential to be used as renewable energy in the form of briquettes. This research was conducted to determine the potential use of plastic powder and biomass as an alternative fuel. The biomass used in this research is rice husk and HDPE plastic. To determine the quality of briquettes, several variations of the mixture of rice husks were used, namely: sample 1 = 90% rice husk + 10% High Density Polyethylene (HDPE) plastic, sample 2 = 80% rice husk + 20% High Density Polyethylene (HDPE) plastic, sample 3 = 70% rice husk + High Density Polyethylene (HDPE) plastic 30%, sample 4 = 100% rice husk. The test parameters used are proximate test (calorific value), flame length test, briquette resistance test. The test results obtained briquettes in sample 3 have a calorific value of 7586,853 cal/g and have a combustion rate value of 0,83 grams/minute.Keywords: Briquettes, Rice Husk, High Density Polyethylene (HDPE) Plastic, Calorific Value